Bioecologia de ácaros (acari) da videira (Vitis vinifera L.) ocorrentes no estado do Rio Grande do Sul, Brasil - Johann, Liana (2014)
Grapevines are attacked by pests and diseases. Under humid conditions, fungal and bacterial diseases are predominant, while in arid regions, the main pests consist of insects and mites. Among the latter, the phytophagous mites are very important. The present work aimed to assess the diversity of mites in vineyards of Cabernet Sauvignon and Pinot Noir varietals in the municipalities of Bento Gonçalves and Candiota, located in the state of Rio Grande do Sul, Brazil; to identify all the stigmaeids at species level and, if necessary, describe unknown species; to know Panonychus ulmi biology in grapevine leaves in the laboratory and the biology of Agistemus floridanus and Neoseiulus californicus feeding on P. ulmi; to evaluate the predators feeding preference and the interactions among the three species; and to build an identification pictorial key for the phytophagous and predatory mites living on grapevines. To evaluate the mite diversity, leaves, buds and non-cultivated plants were sampled between October 2006 and September 2007. In the laboratory, the mites were taken from the leaves, mounted in slides using Hoyer medium and identified with the help of dichotomous keys. All stigmaeids collected were measured and compared to the species already described. Those that presented distinct measures or characteristics were considered new species. Biology of P. ulmi was initiated with 30 eggs kept on Cabernet Sauvignon leaves and 30 eggs kept on Pinot Noir leaves. The immature phases were observed three times per day, and the adult phase only once a day. The biology of the predators was initiated with 30 N. californicus eggs and 30 A. floridanus eggs, and the same observation method was used. The data generated was used to build fertility life tables. Agistemus floridanus and N. californicus feeding preference was assessed by offering them P. ulmi eggs, immature individuals and adults. In order to evaluate their behavior in the presence of P. ulmi and of conspecific and heterospecific odors, each predatory species was given two choices with different odor sources, and their populations were observed after N. californicus was liberated in the field. To make the pictorial key, the diagnostic characteristics were used to distinguish the families and the species, with representative illustrations. The results indicate that species richness and abundance are higher in Bento Gonçalves than in Candiota. Seven Stigmaeidae species live in vineyards in Rio Grande do Sul state: Agistemus brasiliensis, A. floridanus, Agistemus mendozensis, Agistemus riograndensis, Zetzellia agistzellia, Zetzellia malvinae and Zetzellia ampelae. Panonychus ulmi presents an adequate development on grapevine leaves, although its oviposition period and female longevity were both shorter than expected. The Cabernet Sauvignon variety seems to be more adequate than Pinot Noir. Agistemus floridanus and N. californicus completed their development cycle feeding on P. ulmi on grapevines, and presented different life table parameters. Neoseiulus californicus liberation test resulted in a decrease in the number of P. ulmi eggs and mobile forms and in an increase of Agistemus sp. populations, while the number of N. californicus remained stable. The two predators preferred to feed on P. ulmi eggs and responded positively to its presence, and recognized the odor of heterospecific predators. The pictorial key elaborated includes Tetranychidae, Eriophyidae, Tarsonemidae, Tydeidae, Tenuipalpidae, Phytoseiidae, Stigmaeidae and Iolinidae and will be very useful for professionals and researchers who wish to identify mites in the grapevine culture.